4 - Repenser le concept de développement : des impasses d’un processus de standardisation des sociétés à l’émergence d’un sens historique et culturel - Bend, Pauline (Africa Development, 2007)
As it is foisted on Africa, development reflects a very old process of integration into the global community, with the objective to introduce the development val- ues characteristics of western philosophy. This article proposes a critique of what is actually an attempt at standardising societies based on a geographically and historically situated model. It follows with an analysis of the principal currents of thought impacting on the area of development. It interrogates the very concept of development thinking through the challenges being faced by societies aiming for development. Is standardisation possible? Is it not then necessary to redefine development by imbuing its meaning with the context of the human societies it is being tried? And formulate an alternative as a precondition to support a unifying project. It would involve the re-emergence of universality, which does not apply the same development tools to every society, but whose meaning drives all hu- man societies, to think of their future, to propose solutions to problems they face, giving birth to a society project through the implementation of pertinent public policies.